Microwave vacuum drying of lotus (Nelumbo nucifera Gaertn.) seeds: Effects of ultrasonic pretreatment on color, antioxidant activity, and rehydration capacity - Zhao, Yingting; Zhu, Hongzhang; Xu, Jingxin; Zhuang, Weijing; Zheng, Baodong; Lo, Y. Martin; Huang, Zijian; Tian, Yuting (Food science & technology, 2021)
Arguably the oldest method human use to extent the shelf life of food, drying inevitably inherits undesirable physiochemical changes due mainly to how the moisture in food is removed. The present study investigated how ultrasonic pretreatment (UP) affected the color, antioxidant capacity, and rehydration kinetics of lotus seeds (LSs) subjected to subsequent microwave vacuum drying (MVD). Samples of LSs were subjected to UP at intensities of 6.08, 8.39, and 10.84 W/cm2 for 10 min, followed by MVD. UP at the highest intensity (10.84 W/cm2) changed color by increasing L* and b* but decreasing a* and also improved antioxidant activities by enhancing hydroxyl and superoxide anion radical-scavenging activities of microwave vacuum dried LSs. These changes were correlated with the increasing of gallic acid by 17.57%, chlorogenic acid by 106.73%, caffeic acid by 47.80%, rutin by 105.07%, but decreasing the content of p-hydroxybenzoic acid by 15.47% as compared to Fresh-MVD (fresh LSs dried by MVD). Under higher ultrasonic intensity, more notches and grooves appeared on surface of dried LSs which were observed by field emission scanning electron microscopy, which increased rehydration rate. Therefore, ultrasonic technique can be employed as a pretreatment method before the drying operation in order to retain the quality of the dried products. •The effect of ultrasonic pretreatment (UP) on quality of dried lotus seeds (LSs) was studied.•Increase in L* and b* but decrease in a* value resulted in LSs after UP.•Antioxidant activities of LSs peaked at the highest ultrasonic intensity.•Antioxidant activities changed in LSs after UP was attributed to phenolic content.